Insights into the fermentation process of fresh and frozen dough bread made with alginate-immobilized S. cerevisiae yeast cells. (September 2022) - Mihaly Cozmuta, L.; Nicula, C.; Peter, A.; Apjok, R.; Jastrzębska, A.; Mihaly Cozmuta, A.
Abstract: The study reveals the influence of ascorbic acid and salt on the fermentation of fresh and frozen doughs made with free and alginate-immobilized yeast cells. The evolution profiles of Saccharomyces cerevisiae, the redox potential, pH, and specific volume were monitored and the most suitable conditions that resulted in bread loaves being highly accepted by consumers were selected. For fresh doughs, the maximum specific volumes were recorded for the dough made with free yeast cells (DYD-3.0), 6 g NaCl/kg of flour, and 0.5 g ascorbic acid/kg of flour, combining a negative redox potential (−3 mV), a pH of 4.07, and 2 h of proofing. The highest specific volume for the 3-months freezing dough with immobilized yeast cells (CAYD-1.3) requires 6 g NaCl/kg of flour, 1 g ascorbic acid/kg of flour, and combines a negative redox potential (−2 mV), a pH of 3.82, and 2 h of proofing. The bread loaf from CAYD-1.3 received the highest average score for the overall acceptability which is higher than that given to the bread baked from fresh dough DYD-3.0. Graphical abstract: Image 1 Highlights: Fermentation diagrams for S. cerevisiae, redox potential, pH and specific volume in fresh and frozen doughs were built. Optimal fermentation parameters improved sensory attributes of immobilized yeast-based frozen dough bread were extracted. The excess salt negatively influenced the sensory attributes of immobilized yeast-based frozen dough bread. Negative redox potential and ascorbic acid favored the sensory attributes of immobilized yeast-based frozen dough bread. Immobilized yeast-based frozen dough bread showed improved sensory attributes compared with free yeast-based fresh bread.